Induction of depressed mood disrupts emotion regulation neurocircuitry and enhances pain unpleasantness - Berna, C; Leknes, S; Holmes, E; Edwards, R; Goodwin, G; Tracey, I (Elsevier, 2010)
Background: Depressed mood alters the pain experience. Yet, despite its clear clinical relevance, little is known about the cognitive and neural mechanisms underlying this phenomenon. We tested an experimental manipulation to unravel the interaction between depressed mood and pain. We hypothesized that dysregulation of the neural circuitry underlying emotion regulation is the mechanism whereby pain processing is affected during depressed mood. Methods: Using functional magnetic resonance imaging, we compared the effects of sad and neural cognitive mood inductions on affective pain ratings, pain-specific cognitions, and central pain processing of a tonic noxious heat stimulus in 20 healthy volunteers. Results: The increase in negative pain-specific cognitions during depressed mood predicted the perceived increase in pain unpleasantness. Following depressed mood induction, brain responses to noxious thermal stimuli were characterized by increased activity in a broad network including prefrontal areas, subgenual anterior cingulate cortex, and hippocampus, as well as significantly less deactivation when compared with pain responses in a neutral mood. The participants who reported the largest increase in pain unpleasantness after the sad mood induction showed greater inferior frontal gyrus and amygdala activation, linking changes in emotion regulation mechanisms with enhancement of pain affect. Conclusions: Our results inform how depressed mood and chronic pain co-occur clinically and may serve to develop and translate effective interventions using pharmacological or psychological treatment.